Sandwich Generation Career Analysis - Devy, Gita Septyanisa; Linando, Jaya Addin; Suhartini, Suhartini (UNIVERSITAS PAKUAN, 2025)
Sandwich generation conflict occurs when individuals face challenges due to dual roles to balance the demands of work and family responsibilities. This study aims to analyze the status of the sandwich generation affecting individual careers, as well as to find out the inhibiting factors and drivers of the career development of the sandwich generation. Using qualitative methods, this study obtained data through interviews with 15 informants. There are negative results in the results of the sandwich generation's status on individual career development, namely individuals have a burden because they finance their own lives as well as their families and delay career development because they prioritize family responsibilities. The positive result of the sandwich generation status on career development is high work motivation. There are inhibiting factors, namely the sandwich generation often postponing career aspirations or further education due to urgent family needs and stress due to double demands. In addition, there are driving factors, namely support from superiors who focus on performance without considering personal conditions, support from colleagues in the form of encouragement to participate in certification/skill development, and fellow sandwich generations who support each other emotionally and help focus on work